«Building Up a Community School Together»: Relational Strategies Between the School and the Family - Pastor Fasquelle, Roxana (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2018)
In this article I present some experiences carried out in the initial training of early childhood educators. These experiences illustrate diverse models of cooperation between school centres and universities beyond the teaching placement. This collaboration contributes to develop a significant learning and provides real contexts where undergraduate students may apply the theoretical contents acquired at the university. The theoretical background of these initiatives is firstly presented and then the implementation process described. As a conclusion I may say that this collaboration benefits all the agents implied and lays the background for an effective action-research.